2011
DOI: 10.1111/j.1523-5378.2011.00879.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Cancer: Basic Aspects

Abstract: Gastric cancer (GC) is a world health burden, ranging as the second cause of cancer death worldwide. Etiologically, GC arises not only from the combined effects of environmental factors and susceptible genetic variants but also from the accumulation of genetic and epigenetic alterations. In the last years, molecular oncobiology studies brought to light a number of genes that are implicated in gastric carcinogenesis. This review is intended to focus on the recently described basic aspects that play key roles in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(39 citation statements)
references
References 74 publications
(86 reference statements)
0
39
0
Order By: Relevance
“…This model assumes the sequence of precancerous lesions as a dynamic process from an initial superficial inflammation caused by Helicobacter pylori (H. pylori) infection to a fully malignant neoplasm of the stomach. Thus, the chronic infection of the gastric mucosa by the H. pylori, which colonize approximately 50% of the human population, is considered the strongest known risk factor for the development of gastric cancer [6,7] . Ooi et al [8] identified three signaling pathways (nuclear factor-kB, Wnt/b-catenin, and proliferation/stem cell) that were deregulated in more than 70% of the patients diagnosed with gastric cancer, resulting in increased inflammatory cytokine production, abnormal apoptosis, undesirable epithelial cell proliferation/differentiation, and epithelial cell transformation.…”
Section: Introductionmentioning
confidence: 99%
“…This model assumes the sequence of precancerous lesions as a dynamic process from an initial superficial inflammation caused by Helicobacter pylori (H. pylori) infection to a fully malignant neoplasm of the stomach. Thus, the chronic infection of the gastric mucosa by the H. pylori, which colonize approximately 50% of the human population, is considered the strongest known risk factor for the development of gastric cancer [6,7] . Ooi et al [8] identified three signaling pathways (nuclear factor-kB, Wnt/b-catenin, and proliferation/stem cell) that were deregulated in more than 70% of the patients diagnosed with gastric cancer, resulting in increased inflammatory cytokine production, abnormal apoptosis, undesirable epithelial cell proliferation/differentiation, and epithelial cell transformation.…”
Section: Introductionmentioning
confidence: 99%
“…The high mortality of GC is explained by our poor understanding of its mechanism of progression and the lack of suitable diagnostic markers that hinder diagnosis before the disease reaches an advanced stage (7,8). GC represents a biologically and genetically heterogeneous group of tumours that are induced by multiple factors that deregulate cell signalling pathways, which leads to the acquisition of malignant phenotypes such as increased cell proliferation, inhibition of apoptosis and enhanced invasiveness (9)(10)(11). Identification of novel molecules is therefore required to improve diagnosis and therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Helicobacter pylori (H. pylori) infection is involved in the early stage of gastric cancer pathogenesis by inducing chronic gastritis (3)(4)(5)(6). This chronic gastritis can persist for decades and may result in nonresolving inflammation, which is a major driver of gastric cancer (6), and the interaction of host-pathogen contributes to this carcinogenesis (7).…”
Section: Introductionmentioning
confidence: 99%